Experiencing nature: the Spanish American empire and the early scientific revolution - Barrera-Osorio, Antonio (Univ. of Texas Press, 2006)
Searching the land for commodities -- A chamber of knowledge: the Casa de la Contrataciòn and its empirical methods -- Communities of experts: artisans and innovation in the New World -- Circuits of information: reports from the New World -- Books of nature: scholars, natural history, and the New World -- Conclusions: the politics of knowledge -- Appendix 1. Pilots and cosmographers at the Casa de la Contrataciòn -- Appendix 2. Instruments -- Appendix 3. Spanish scientific books.